[Rezension von: Persianism in antiquity] - Waters, Matt (JAOS, 2023)
Persianism in Antiquity. Edited by Rolf Strootman and MigueL John Versluys. Oriens et Occidens, vol. 25. Stuttgart: Franz Steiner Verlag, 2017. Pp. 557, illus. €84.